2019
DOI: 10.3390/toxins12010021
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Lactic Acid Bacteria to Reduce Aflatoxin B1 and Fumonisin B1 Occurrence on Corn Kernels and Corn Ears

Abstract: Fungal spoilage is an important issue for the food industry, leading to food sensory defects, food waste, economic losses and public health concern through the production of mycotoxins. Concomitantly, the search for safer natural products has gained importance since consumers began to look for less processed and chemically treated foods. In this context, the aim of this study was to evaluate the antifungal and antimycotoxigenic effect of seven strains of Lactobacillus plantarum. Lactic acid bacteria (LAB) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…For instance, Aflatoxin B1, Ochratoxin A, and Zearalenone have been associated with hepatotoxicity, nephrotoxicity, and hyperestrogenism [12,13]. Besides, based on recent reports, mycotoxin prevalence could be as high as 60-80% in food [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Aflatoxin B1, Ochratoxin A, and Zearalenone have been associated with hepatotoxicity, nephrotoxicity, and hyperestrogenism [12,13]. Besides, based on recent reports, mycotoxin prevalence could be as high as 60-80% in food [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids produced by Lactiplantibacillus plantarum (formerly Lactobacillus plantarum ) are involved in the antifungal activity or in the reduction of aflatoxin production in e. g. maize (Nazareth et al . 2020 ). In other cases, antifungal compounds produced by LAB are peptides by chemical nature, such as those against Aspergillus flavus on maize (Muhialdin et al .…”
Section: Antifungal Compoundsmentioning
confidence: 99%
“…Other sources have report this anti-mycotoxigenic activity from other LAB strains. In the work of Nazareth et al [36], the production of several metabolites in a CFS fermented by Lactobacillus plantarum CECT 749 has been linked to a reduction of aflatoxin B 1 and fumonisin B 1 in corn contaminated by A. flavus and F. verticillioides. Guimarães et al [37] also reported anti-aflatoxigenic activity in vitro related with compounds such as lactic acid, PLA, hydroxyphenyllactic acid, and indol acetic acid present in CFS fermented by L. plantarum UM55 against Aspergillus parasiticus and A. flavus.…”
Section: Metabolite Profiling Of Fungal Growth On Grapementioning
confidence: 99%